Foreign Direct Investment in the Visegrad Countries after 2004: Have the Visegrad Countries’ Membership in the European Union Changed Something? - Jacek Klich (Entrepreneurial Business and Economics Review)
The purpose of the paper is to identify the volume and dynamics of FDI in the Czech Republic, Hungary, Poland and Slovakia (V4) after their full accession to the European Union. The following hypothesis is tested: the Visegrad countries’ membership in the European Union has not resulted in higher increases of FDI in these countries. The methodology is based on the concept of Investment Development Path (IDP) and Net Outward Investment position (NOI) of a country. The most current data (as of 2012) on FDI is derived from UNCTAD. The literature available in ScienceDirect and EBSCO has been reviewed.